Experimental study of steel moment resisting frames with shear link. (March 2019) - Mahmoudi, Farid; Dolatshahi, Kiarash M.; Mahsuli, Mojtaba; Nikoukalam, Mohammad T.; Shahmohammadi, Amir
Abstract: Seismic codes specify a minimum beam span-to-depth ratio for moment resisting frames to ensure formation of plastic hinges at beam ends with adequate length. This minimum beam span-to-depth limitation is at odds with the need for shorter spans to control lateral drifts in tall buildings, especially with tubular frames. To ease the limitation, this paper proposes a shear link at the beam mid-span, comprising a replaceable beam with a smaller cross-section than that of the main beam. The shear fuse dissipates energy by shear yielding and thus, prevents or delays the flexural yielding of beam ends. To examine the proposed idea, a moment resisting frame that violates the minimum beam span-to-depth ratio limitation and a hybrid frame (HF) with the proposed fuse are subjected to cyclic loading in laboratory experiments. The results indicate adequate energy dissipation and stable hysteresis behavior for Specimen HF, thereby eliminating the need to observe the code limitation. Specimen HF shows a ductility capacity twice that of the moment resisting frame with almost the same stiffness and strength. Additionally, replaceability of the fuse enhances the resilience of the proposed system. Finally, a numerical model is developed and verified with the test results for future expansion of the proposed design concept. Highlights: A shear link is proposed at the middle of the beam span to change the nonlinear behavior of short span frames. The frame can be tuned to have hybrid shear-flexural nonlinear behavior. Design procedure is presented for the proposed system. A numerical model is presented and verified against the experimental results.